Olive oil and hydration based on clinical assessment and transepidermal water loss: A systematic review - Paramitha Jaya, Ni Made Ayu Nadia; Hermawan, Melyawati; Regina, Regina (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Dry skin or xerosis is a layer of skin that loses moisture due to increased transepidermal water loss (TEWL). Olive oil, one of the most commonly available moisturizers, is often used to keep the skin hydrated. Skin hydration indicates the amount of water in the stratum corneum. This systematic review aimed to determine the association between olive oil application and skin hydration based on clinical assessment and TEWL parameters. Methods: The research design used was a systematic review based on the criteria of preferred reporting items for systematic reviews and meta-analyses (PRISMA). This systematic review search used PubMed, ProQuest, Google Scholar, CINAHL, and NLM Catalog databases. The risk of bias in the literature used in this study was assessed using the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2). Results: Five articles were included in this systematic review in which topical intervention on the skin was used with olive oil and other oils, placebo, or no therapy as controls. Olive oil can improve skin conditions clinically and provide various beneficial effects such as antioxidants and anti-inflammatory, but the oleic acid content, which is the main component of olive oil, has detrimental effects on the skin. Conclusion: This systematic review reveals that olive oil can improve skin condition clinically, but long-term topical application of olive oil may damage the integrity of the skin and increase TEWL.